Training students as interprofessional learning facilitators: An exploratory study highlighting the need to build confidence. Issue 4 (4th July 2018) - Baker, Becky; Drane, Coral; Chambers, Joshua; Lindqvist, Susanne
ABSTRACT: Interprofessional learning (IPL) aims to equip students for future interprofessional and collaborative practice. Involving students as IPL facilitators is becoming increasingly commonplace as an attempt to catalyse the necessary transformation of our workforce needed to deliver truly integrated and person-centred care. Evidence in the literature highlights the key role of trained facilitators in reaching successful IPL outcomes. Some guidelines are available as to how we train staff facilitators, but little evidence is available that describes how to appropriately prepare student IPL facilitators. The aim of this exploratory study was to investigate whether student IPL facilitators felt that they were sufficiently prepared for their role. Data in the form of open-ended text-based responses from student facilitators (n = 9) were collated after an intervention where student facilitators had been given the role of supporting IPL. Data were analysed using principles of thematic analysis. Three main themes emerged: i) building confidence; ii) purpose of IPL; iii) learning moments. Student IPL facilitators who took part in this study felt that they were adequately prepared for their role. Findings show that preparing students for IPL facilitation has similar, yet unique, components compared to the training staff. In particular, this study highlighted a need for student facilitators to receive further preparation to help build their confidence. Involving students as IPL facilitators has great potential in staff and students joining forces to equip students for future interprofessional and collaborative practice that can deliver high-quality care.